Pemetaan Potensi Desa Aur Sati Kabupaten Kampar Provinsi Riau - Monita Olivia; Ferry Fatnanta; Gunawan Wibisono; Muhammad Ikhsan; Iskandar Romey Sitompul; Rizqy Ridho Prakasa (Riau Journal of Empowerment, 2024)
Mapping village potential is an important aspect of sustainable rural development. It allows village governments and communities to optimize resource management and improve community welfare. In general, community service activities are designed into three stages, namely preparation, activity implementation, and evaluation and aim to conduct comprehensive village potential mapping. The community service activities involve active participation of the community and village officials in Focus Group Discussions (FGDs) to identify, document, and map all aspects of village potential. This method aims to empower village communities in regional development by producing comprehensive data on existing village potential. The resulting village potential map becomes an invaluable tool for village governments in sustainable development planning and village asset management. Through this village potential mapping, Aur Sati Village is expected to optimize its opportunities to improve community welfare and develop its regional characteristics, including tourism, agriculture, and fisheries potential.